Chlorine inhalation‐induced myocardial depression and failure. Issue 6 (June 2015) - Zaky, Ahmed; Bradley, Wayne E.; Lazrak, Ahmed; Zafar, Iram; Doran, Stephen; Ahmad, Aftab; White, Carl W.; Dell'Italia, Louis J.; Matalon, Sadis; Ahmad, Shama
Abstract Victims of chlorine (Cl2) inhalation that die demonstrate significant cardiac pathology. However, a gap exists in the understanding of Cl2‐induced cardiac dysfunction. This study was performed to characterize cardiac dysfunction occurring after Cl2 exposure in rats at concentrations mimicking accidental human exposures (in the range of 500 or 600 ppm for 30 min). Inhalation of 500 ppm Cl2 for 30 min resulted in increased lactate in the coronary sinus of the rats suggesting an increase in anaerobic metabolism by the heart. There was also an attenuation of myocardial contractile force in an ex vivo (Langendorff technique) retrograde perfused heart preparation. After 20 h of return to room air, Cl2 exposure at 500 ppm was associated with a reduction in systolic and diastolic blood pressure as well echocardiographic/Doppler evidence of significant left ventricular systolic and diastolic dysfunction. Cl2 exposure at 600 ppm (30 min) was associated with biventricular failure (observed at 2 h after exposure) and death. Cardiac mechanical dysfunction persisted despite increasing the inspired oxygen fraction concentration in Cl2‐exposed rats (500 ppm) to ameliorate hypoxia that occurs after Cl2 inhalation. Similarly ex vivo cardiac mechanical dysfunction was reproduced by sole exposure to chloramine (a potential circulating Cl2 reactant product). These results suggest an independent and distinctive role of Cl2 (and its reactants) in inducing cardiac toxicity and potentially contributing to mortality.